Impact of rotavirus vaccination on diarrheal hospitalizations in children younger than 5 years of age in a rural southern Mozambique - Manjate, Filomena (2022)
Funding Information: We thank the participants in this study and their parents for allowing the collection of samples and data. The authors would also like to thank all Centro de Investigação em Saúde de Manhiça (CISM) staff particularly those supporting Diarrheal Disease Research Area and Manhiça District Hospital. Core funding for CISM is provided by the Spanish Agency for International Cooperation and Development (AECID). ISGlobal receives support from the Spanish Ministry of Science and Innovation through the “Centro de Excelencia Severo Ochoa 2019-2023” Program (CEX2018-000806-S), and support from the Generalitat de Catalunya through the CERCA Program. The GEMS study was supported by the Bill & Melinda Gates Foundation (Project OPP 38874). The impact of rotavirus study was supported by GAVI funds through Centers for Disease Control and Prevention Foundation (CDCF), Atlanta & World Health Organization, Regional Offices for Africa (WHO AFRO). The funders had no role in the study design, data collection and analysis, decision to publish, or preparation of the manuscript. The findings and conclusions of this report are those of the authors and do not necessarily represent the official position of the US Centers for Disease Control and Prevention and World Health Organization. The authors declare no conflict of interest. Funding Information: We thank the participants in this study and their parents for allowing the collection of samples and data. The authors would also like to thank all Centro de Investigação em Saúde de Manhiça (CISM) staff particularly those supporting Diarrheal Disease Research Area and Manhiça District Hospital. Core funding for CISM is provided by the Spanish Agency for International Cooperation and Development (AECID). ISGlobal receives support from the Spanish Ministry of Science and Innovation through the “Centro de Excelencia Severo Ochoa 2019-2023” Program (CEX2018-000806-S), and support from the Generalitat de Catalunya through the CERCA Program. The GEMS study was supported by the Bill & Melinda Gates Foundation (Project OPP 38874). The impact of rotavirus study was supported by GAVI funds through Centers for Disease Control and Prevention Foundation (CDCF), Atlanta & World Health Organization, Regional Offices for Africa (WHO AFRO). The funders had no role in the study design, data collection and analysis, decision to publish, or preparation of the manuscript. Publisher Copyright: © 2022